Diяty. Issue 3 (3rd July 2019) - Fox, Ragan
ABSTRACT: This is an autoethnographic account of child molestation. I use "dirty work" as a methodological instrument to explore the ethics and nuances of recalling and writing about child sex abuse. The essay also investigates intra-familial communicative breakdowns that often emerge after child sex abuse survivors disclose mistreatment they have endured.